Peningkatan kapasitas dan penilaian mandiri kinerja pelayanan publik - Aristanto, Eko; Damayanti, Indri (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The implementation of this activity aims to increase the capacity of public service providers in carrying out public services and assist in carrying out an self assessment of the performance of public services.Training and mentoring activities are followed by public service providers in Balai Besar Pelaksanaan Jalan Nasional VIII Jawa Timur. Methods of carrying out activities that include: i) Desk documents; ii) Training; and iii) Assistance. The implementation of activities begins and is based on the evaluation results of the PANRB Ministry. The output of the implementation of this activity can contribute to improving the performance of public services with the support and availability of various public service documents including: public service standard documents, improving the implementation of public satisfaction surveys, and improving public service information on the BBPJN VIII website. The results of the training and mentoring show an increase in the performance of public services from 2.72 (Score C) to 3.50 (Score B). The evaluation of training and mentoring activities showed a result of 88.67% with very good training performance.